Shahīd Bhuṭṭo : ṣadiyoṉ kī ṣadā : qāʼid-i ʻavām shahīd Ẕūlfaqār ʻAlī Bhuṭṭo kī 30 veṉ barsī . - Meman, Yāsmīn; Bhutto, Zulfikar Ali, 1928-1979 (Maḥkamah-yi It̤t̤ilaʻāt, Ḥukūmat-i Sindh, 2009)
Commemorative volume on the life of Zulfikar Ali Bhutto ex-Prime Minister of Pakistan; contributed articles.